203k views
0 votes
X+3x-y+y+2z+z

help please its my rsm homework

User AvcS
by
5.2k points

2 Answers

5 votes

Answer:

the answer is 4x + 3z

Explanation:

1x + 3x + -1y + 1y + 2z + 1z

1x + 3x = 4x

-1y + 1y = 0

2z + 1z = 3z

so the answer is 4x + 3z

User Hovenko
by
5.6k points
0 votes
To simplify the given expression, we need to combine like terms. This would look like:

x + 3x - y + y + 2z + z

→ 4x + 3z

In this expression, y cancels out because -1 + 1 = 0, and would therefore have no value.

Answer Recap: The simplified version of this expression would be:

→ 4x + 3z
User Louay Alakkad
by
5.4k points